Propuesta de un plan de comunicación interna orientada a mejorar el proceso de planificación estratégica en la empresa SCGV Cía. Ltda., con el uso de las tics como herramienta aplicada a la administración. - Valencia Maldonado, Guillermo Antonio (2014)
This research "Proposal of an internal communications plan aimed at improving the strategic planning process in the company SCGV Cia. Ltda. With the use of the tool tics as applied to management. ", Aims targeted internal customer communication, which is a topic of great interest to employers and the general public. Today companies give more interest to internal communication, how we lead, manage financial, human and material resources; leaving unnoticed customer service and how important we do not take our competition is growing as their client; because of the good service and care provided; For this we have done surveys to all employees of the company which allowed determining who has an incorrect internal communication, not worry about the customer service that is taking place in the company, because the manager is to lead the way the company and therefore it is proposed to design an internal communication system to improve customer service company.